Air co-gasification of coal and dried sewage sludge in a two-stage gasifier: Effect of blending ratio on the producer gas composition and tar removal. (15th October 2019) - Jeong, Yong-Seong; Choi, Young-Kon; Park, Ki-Bum; Kim, Joo-Sik
Abstract: The co-gasification of coal and dried sewage sludge (DSS) was conducted using a two-stage gasifier consisting of a fluidized bed gasifier and a tar-cracking reactor. In this study, the effect of the blending ratio of coal and DSS was investigated. Producer gases that were obtained from the tar-cracking reactor filled with active carbon contained high levels of hydrogen (maximum H2 : 27.7 vol%) and low tar contents (minimum tar: 0 mg/Nm 3 ). Upon gasification of the coal/DSS blends, the hydrogen content decreased and tar content increased with increasing DSS. Blends with coal/DSS ratios of 70/30 and 50/50 showed a synergetic effect on tar reduction, which could be attributed to the high ash content of the DSS. The gasification of the 70% DSS blend increased the condensed tar yield by only 0.1 wt%, compared to coal gasification. Lastly, a hot filter filled with Fe-impregnated active carbon was applied to completely remove tar from producer gas, which led to the production of a tar-free and hydrogen-rich gas (30 vol%). Furthermore, the Fe-impregnated active carbon reduced the H2 S content to 229 ppmv. In summary, it was possible to produce a clean gas from coal and DSS blends in the UOS gasification process. Highlights: The co-gasification was performed using a two-stage gasifier with active carbon. Coal gasification produced a tar-free gas having 27.7 vol% H2 . Tar-free gas could be obtained from the co-gasification of 30% DSS blend. Gasification of 70% DSS blend increased condensed tar yield only by 0.1 wt%. Fe-impregnated active carbon produced a tar-free gas having 30 vol% H2 .